Universality and identity politics - McGowan, Todd (Columbia University Press, 2020)
"We live amid countless claims for the importance of identity and an almost equal number of critiques of identity politics. Identity has become the privileged terrain for political struggle in contemporary society. For many on the Left, the turn from class politics to identity politics is something to lament. They argue for a return to a political critique of capitalist economics, which should have a position of primacy, they contend, relative to questions of identity. For conservatives, in contrast, identity politics marks a further radicalization of the Left, a triumph of what they erroneously call Cultural Marxism. Todd McGowan intervenes in these debates by offering as an alternative a new theory of universality that avoids the totalizing vision of previous homogenizing Eurocentric varieties. For McGowan, what unites us is not an ethics or a politics with which we all must agree but instead what we lack as political subjects who under conditions of capitalism cannot fully be who we are. This lack is the foundation of every emancipatory political project. In repositioning the debate between universality and identity in a new register, he shows that the real proponents of identity politics are the right-wing nationalist, ethnic, and religious fundamentalists who unite against their perceived enemies"--